« The glittering game » : le jeu des choses dans A Lost Lady et My Mortal Enemy de Willa Cather - Céline Manresa (Transatlantica)
In A Lost Lady and My Mortal Enemy, Willa Cather endows things with an active role in the plots and a new relief in her writing. Far from remaining hidden in the background of settings, things occupy the foreground of the diegetic and narrative spaces. From the details of costumes to the decoration of houses, material possessions play an essential part in the reciprocal shaping of dwellers and dwellings, and in the dramatization of a bygone splendor. Objects delineate and emblematize the magnificence of the drawing-rooms in which Marian and Myra exhibit themselves like precious jewels. Now, in her two novels, the writer also shows how things constantly alter the progression of the plots and the relationships between the characters. During the house parties at the Forresters’ or the Henshawes’, objects keep circulating among the hands of neighbors, friends, or lovers to weave clandestine alliances and rekindle the games of power, seduction and deception. In A Lost Lady as in My Mortal Enemy, Cather thus develops a theatrical and poetic play with and around things.